Kepemilikan Institusional, Keragaman Dewan, dan Pengungkapan Emisi Karbon - Budanti, Ni Putu Lion; Rustiarini, Ni Wayan; Putra, I Gede Cahyadi (Universitas Airlangga, 2024)
Global warming is a crucial issue that is being discussed today. One of the causes of global warming is the development of the industrial sector, which contributes to greenhouse gas emissions. This condition requires public companies to disclose carbon emissions. This study explores the role of institutional ownership and board diversity in carbon emission disclosure (CED) in Indonesia. Board diversity refers to the female and foreign director variables. The study was conducted on manufacturing companies over three years and data analysis using moderated regression analysis. The study results revealed that institutional ownership increased CED. Nevertheless, board diversity testing as a moderation variable provides inconsistent results. The results of the interaction test revealed that the existence of female directors was able to moderate the relationship between institutional ownership and CED. Conversely, foreign directors cannot moderate the relationship between institutional ownership and CED.